JENIS DAN KELIMPAHAN PLANKTON DI PANTAI DOSA, KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - Sulfiana Wing Putri; Alianto; Philipus Musyeri; Wikram (Nusantara Hasana Journal, 2023)
Plankton in aquatic ecosystems has a very important role, especially in the food chain, because plankton is the main producer that makes the largest contribution to the total primary productivity of an aquatic area. This Field Work Practice aims to determine the species and abundance of plankton that is good and correct according to widely used standards. This Field Work Practice was carried out on 10 January – 10 February 2023. Determination of field work practice stations using the purposive sampling method at 1 location and three plankton sampling points. In situ measurement of water quality parameters includes temperature, dissolved oxygen (DO), pH and salinity. Plankton samples were identified and analyzed at the Aquatic Resources Laboratory, Faculty of Fisheries and Marine Sciences, University of Papua. The results of field work practice obtained eight classes of plankton and classes consisting of 33 genera. Phytoplankton found 29 genera from 5 classes namely Bacillariophyceae, Cyanophyceae, Chlorophyceae, Dinophyceae, Trebouxiophyceae, And Zooplankton found 3 classes consisting of 4 genera, namely Scyphozoa, Copepoda, Eurotatoria. The highest abundance of Phytoplankton was at seagrass points, namely 1005 Sel/L, coral reefs 637.5 Sel/L and mangroves 530 Sel/L. The highest abundance of Zooplankton was found in seagrasses around 40 individu/L, coral reefs with 10 individu/L, and mangroves with 0 individu/L.